Identification of the thrombin receptor on human platelets by chemical crosslinking. - Takamatsu, J (1986)
To identify the molecular site of thrombin binding to the platelet membrane, we covalently linked 125I-thrombin to platelets by using the bifunctional chemical cross-linking agents disuccinimidyl suberate and dithiobis(succinimidyl propionate). The proteins cross-linked to 125I-thrombin by this method were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and followed by autoradiography. Two radiolabeled thrombin complexes were identified, a major species of Mr approximately 200,000 and a minor one of Mr approximately 400,000. Hirudin prevented the formation of both complexes. The radioactivity of the approximately 200,000-Mr complex was always 7-10-fold greater than the radioactivity of the approximately 400,000-Mr complex regardless of the thrombin concentration to which the platelets were exposed (0.1-29 nM). Although 125I-thrombin complexes generated with thrombasthenic platelets (lacking glycoprotein IIb/IIIa) were indistinguishable from normal, no complexes appeared when Bernard-Soulier platelets (lacking glycoprotein Ib [GPIb]) were used. Complex formation was blocked by rabbit antiglycocalicin antiserum, but not by the monoclonal antibody 6D1, which is directed against the site on GPIb where von Willebrand factor (vWf) binds in the presence of ristocetin. Although cross-linking studies suggested that vWf might partially inhibit thrombin binding to platelets, this was not confirmed by equilibrium binding studies in the presence of vWf and ristocetin. The data suggest, therefore, that at all thrombin concentrations binding occurs at the same membrane site, despite evidence from equilibrium studies for high and low affinity classes of receptors, and that the approximately 400,000-Mr complex is simply a dimer of the approximately 200,000-Mr species. We conclude that the membrane site to which thrombin binds is the glycocalicin portion of platelet GPIb at a site remote from the point of ristocetin-dependent vWf binding.